2019
DOI: 10.3126/jucms.v7i1.24680
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Central Obesity with Overall Obesity in Predicting the Risk of Type 2 Diabetes Mellitus

Abstract: INTRODUCTION: Many studies have shown the association of waist circumference, waist hip ratio and body mass index with type 2 diabetes mellitus. Waist circumference and waist hip ratio have been used as measures of central obesity and body mass index has been used as a measure of general obesity. Objective of this study is to find out which type of obesity is better for prediction of risk of type 2 diabetes mellitus.  MATERIAL AND METHODS:Total 100 participants with confirmed diagnosis of type 2 DM with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Many studies have shown the association of waist circumference, waist hip ratio and body mass index with type 2 diabetes mellitus. Waist circumference and waist hip ratio have been used as measures of central obesity and body mass index has been used as a measure of general obesity [13]. Recently, waist-to-height ratio (WHtR) was suggested as a simpler indicator of abdominal obesity that has greater practical advantages than BMI and WC [14].…”
Section: Anthropometricsmentioning
confidence: 99%
“…Many studies have shown the association of waist circumference, waist hip ratio and body mass index with type 2 diabetes mellitus. Waist circumference and waist hip ratio have been used as measures of central obesity and body mass index has been used as a measure of general obesity [13]. Recently, waist-to-height ratio (WHtR) was suggested as a simpler indicator of abdominal obesity that has greater practical advantages than BMI and WC [14].…”
Section: Anthropometricsmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a metabolic disorder characterized by hyperglycemia, insulin resistance, defects in insulin secretion, insulin action or both. 1 Type 2 diabetes mellitus is more common than type 1 diabetes mellitus and is associated with comorbid conditions like hypertension, dyslipidemia, depression. 2 Various studies have shown an increased incidence of depression in patients with type 2 diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%